Trends on Integrating Framework of Applications or Data - Bricon-Souf, N.; Conchon, E.; Section Editors for the IMIA Yearbook Section on Health and Clinical Management (Yearbook of Medical Informatics, 2014)
Objective: To summarize current excellent research and trends in the field of Health and Clinical management.Methods: Synopsis of the articles selected for the IMIA Yearbook 21014Results: A comprehensive review of papers published in 2013 was performed by querying PubMed. 1079 were reviewed as papers without authors, without abstract or smaller than 4 pages were excluded from the selection. The editors reviewed all papers and 15 papers selected and provided to to international reviewers. Four papers from international peer-reviewed journals were finally selected for the Health and Clinical Management section.Conclusion: Many telemedicine applications are tested nowadays in medical situation, but the challenges emphasized by the best papers selection focus on the ability of proposing integrative frameworks for applications or data in order to handle efficiency of health and clinical management.
Keywords: Health and Clinical Management; patient care management; medical record systems; technologies in healthcare; telemedicine